Records Committee review for rare bird sighting for Eskimo Curlew at Johnson County, IA before 1893 - Iowa Ornithologists' Union Records Committeeet al (1892)
Records Committee review for several Eskimo Curlews at Johnson County, IA before 1893. Includes a record review document with votes, the original sighting record found in the publication Report of committee on state fauna in the Proceedings of the Iowa Academy of Science 1(3): 39-42 by Charles C. Nutting collected by Frank Bond, and referenced by two other publications. Epson - sheet feed